Penyempurnaan Penulisan Al-Qur’an Pasca Khulafa’ Al-Rasyidin: Suatu Tinjauan Historis - Sakti, Irfan Jaya; Basri, Halimah; Miswar, Andi; Ihsan, Muhammad Nurul (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
This research aims to analyze the writing of Al-Qur'an manuscripts after the era of the Khulafa al-Rasyidin as part of the historical development of the Qur'an. The study employs a descriptive qualitative approach based on literature analysis, drawing from linguistic books, academic journals, and other scholarly sources using a historical framework. The primary objective is to explore the early refinements in Qur'anic writing and the different forms of script that emerged after the Khulafa al-Rasyidin. The results of the analysis show that 1) The introduction of diacritical marks and vowelization in the Qur'an after the Khulafa al-Rasyidin was driven by the increasing number of non-Arab Muslims and the expansion of Islamic territories. Additionally, the directive from Governor Ziyad bin Abihi to Abu al-Aswad al-Du'ali played a crucial role in initiating the addition of vowels and dots to the Qur'anic script to prevent mispronunciations. 2) There were two primary developments in the writing of the Qur'an after the Khulafa al-Rasyidin. The first was the introduction of vowel markings (Nuqath al-I'rab) by Abu al-Aswad al-Du'ali, which was later refined by al-Khalil bin Ahmad al-Farahidi (d. 170 AH) by modifying the shape of the vowel marks. The second was the introduction of diacritical dots (Nuqath al-I'jam), with Nahsr bin 'Ashim and Yahya bin Ya'mar being credited for reviving this tradition to differentiate letters with similar shapes. This process led to the development of the al-Ihmal and al-I'jam methods.